Understanding science centre engagement in making an exhibition experience - Baniyamin, Nurhaya; Abdul Rahim, Zaiton (IDOSI Publications, 2017)
Reaching and engaging visitors within exhibitions, as well as throughout the entire museum environment, recurred as an area of design concern and struggle. The paper discusses various science centre methodological approaches to encourage visitor into having a response. This brings effects on visitors’ participation and immersion. The review highlights multiple learning theories underpinning how visitors learn and how these theories impact a museum’s exhibition design efforts. Using the recent experience of The Mind Museum, Philippines, Questacon Australia as primary case-studies and The Experimentarium, Denmark with The Powerhouse Museum as further reference, this paper examines different perspectives and methodological approaches. Nurturing visitor interest through an exhibition experience represents an important recurring concept which strike at the core of the exhibition design process. Visitors act as celebrants of science information in an edutainment context, motivated by a quest for social and enlightening experiences. How do science centre nurture an exhibition experience? How do they support quality visitor experience and informal learning intentions? Answers to these questions are the essence of this paper.